A human Angelman Syndrome class II pluripotent stem cell line with fluorescent paternal UBE3A reporter - Kelkar, Gautami R.; Stuppy, Samantha R.; Sen, Dilara; Yagci, Z. Begum; Han, Linna; Land, Lexi; Hartman, Jessica K.; Keung, Albert J. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionAngelman Syndrome (AS) is characterized in large part by the loss of functional UBE3A protein in mature neurons. A majority of AS etiologies is linked to deletion of the maternal copy of the UBE3A gene and epigenetic silencing of the paternal copy. A common therapeutic strategy is to unsilence the intact paternal copy thereby restoring UBE3A levels. Identifying novel therapies has been aided by a UBE3A-YFP reporter mouse model. This study presents an analogous fluorescent UBE3A reporter system in human cells.MethodsPreviously derived induced Pluripotent Stem Cells (iPSCs) with a Class II large deletion at the UBE3A locus are used in this study. mGL and eGFP are integrated downstream of the endogenous UBE3A using CRISPR/Cas9. These reporter iPSCs are differentiated into 2D and 3D neural cultures to monitor long-term neuronal maturation. Green fluorescence dynamics are analyzed by immunostaining and flow cytometry.ResultsThe reporter is successfully integrated into the genome and reports paternal UBE3A expression. Fluorescence expression gradually reduces with UBE3A silencing in neurons as they mature. Expression patterns also reflect expected responses to molecules known to reactivate paternal UBE3A.DiscussionThis human-cell-based model can be used to screen novel therapeutic candidates, facilitate tracking of UBE3A expression in time and space, and study human-specific responses. However, its ability to restore UBE3A function cannot be studied using this model. Further research in human cells is needed to engineer systems with functional UBE3A to fully capture the therapeutic capabilities of novel candidates.